A multiplex microsatellite tool for conservation genetics of the endemic limpet Patella candei in the Macaronesian archipelagos. Issue 4 (2nd May 2016) - Faria, João; Pita, Alfonso; Rivas, Manuel; Martins, Gustavo M.; Hawkins, Stephen J.; Ribeiro, Pedro; Neto, Ana I.; Presa, Pablo
Abstract: The intertidal limpet Patella candei represents an important exploited resource in the Macaronesian archipelagos of Azores, Madeira and Canaries (NE Atlantic). Despite being considered endemic, the taxonomic status of P . candei throughout the region remains unclear. The aim of this study was to develop novel microsatellite markers using next generation sequencing for the limpet P . candei . Twelve novel loci were described and amplified in 103 individuals from two populations (Azores and Madeira) using three multiplex reactions. The number of alleles per locus ranged from 2 to 14 and global observed heterozygosity was 0.417. Genetic differentiation between samples was highly significant ( F ST  = 0.427) as two main gene pools ( K  = 2) were identified using Bayesian approaches. The present genetic tool can be useful to establish the genetic structuring and patterns of connectivity of P . candei in Macaronesia as well as to determine the number of extant subspecies within the P . candei species complex. Such data will provide a fundamental asset to define stocks and thus inform specific conservation strategies that foster the sustainable exploitation of the P . candei complex throughout Macaronesia archipelagos. Copyright © 2016 John Wiley & Sons, Ltd.